2005
DOI: 10.1111/j.1469-0691.2005.01269.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of two blood culture procedures for the isolation of staphylococci in a paediatric intensive care unit

Abstract: Blood culture results obtained between January 2000 and July 2003 were reviewed for 1360 patients in a paediatric intensive care unit (PICU). The BacT/Alert FA aerobic medium was used with a blood volume of 1.5 mL for the first 23 months, and the BacT/Alert PF paediatric medium was used with a 0.5-mL volume for the remaining 18 months. The isolation rates were similar during both periods (13.4% vs. 13.1%), and staphylococci were the most common isolates (72.8%). There was a shorter time to detection of staphyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…14 In contrast, there was no difference in overall isolation rates between 0.5-mL and 1.5-mL blood cultures (13.4% vs 13.1%) in a recent study that investigated 2 blood culture procedures in a PICU. 29 However, coagulasenegative staphylococci were isolated more commonly with the low-volume blood culture system, and it was not possible to determine whether they were significant or contaminant isolates.…”
Section: Discussionmentioning
confidence: 99%
“…14 In contrast, there was no difference in overall isolation rates between 0.5-mL and 1.5-mL blood cultures (13.4% vs 13.1%) in a recent study that investigated 2 blood culture procedures in a PICU. 29 However, coagulasenegative staphylococci were isolated more commonly with the low-volume blood culture system, and it was not possible to determine whether they were significant or contaminant isolates.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, the BacT/Alert system shows improved positivity rate due to the large volume of blood sampled [1]. Fortunately, it appears that use of very small inoculation volume (down to 0.5 mL) does not compromise isolation rate [8,10], supporting the evidencebased assertion that microbial culture blood volume may be less important in neonates and small children than in adults [11].…”
mentioning
confidence: 92%
“…This situation is beginning to be rectified by clinical laboratory performance studies targeting different populations. During the past dozen years, several observational and experimental trials have indicated that continuous blood culture monitoring permits sensitive and speedy confirmation of bacteremia and fungemia in adults [3,5] and children [6][7][8][9]. A key gap that remains is the paucity of data for neonates.…”
mentioning
confidence: 99%